2017
DOI: 10.1007/s00384-017-2852-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative management of perforated acute diverticulitis with extraluminal air: results and risk factors of failure

Abstract: Nonoperative management of perforated diverticulitis is safe and efficient. Special follow-up must be assumed in patients ASA III-IV and with distant air in CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 13 publications
1
38
0
2
Order By: Relevance
“…Perforated diverticulitis has a higher possibility to become complicated diverticulitis, and complicated diverticulitis accompanied by peritonitis with perforation, intra-abdominal abscess, and fistula formation is well known to require longer hospitalization [ 11 12 13 ]. Our study showed a result similar to that of previous studies: that is, a perforation finding on the CT scan was a statistically significant factor associated with a hospital stay of longer than 6 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perforated diverticulitis has a higher possibility to become complicated diverticulitis, and complicated diverticulitis accompanied by peritonitis with perforation, intra-abdominal abscess, and fistula formation is well known to require longer hospitalization [ 11 12 13 ]. Our study showed a result similar to that of previous studies: that is, a perforation finding on the CT scan was a statistically significant factor associated with a hospital stay of longer than 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel rest is also required for patients with severe symptomatic diverticulitis [ 11 12 13 ]. For such patients, the recommendation is that they stay in an NPO state until symptoms and clinical signs improve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding six studies that did not fulfill the primary end‐point, two studies that were duplicates and three with insufficient data to meet the end‐point. Finally, six studies were included for review . The flowchart of study enrollment is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five patients were excluded because at re-evaluation, no extraluminal air was observed ( n = 25) or the extraluminal air was located more than 5 cm of the affected segment ( n = 10). After exclusion of two duplicate patients, a total of 109 patients were included in the present study; 39 patients from the DIABOLO 14 trial and 70 patients from the retrospective single-centre cohort. Baseline characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%